Sustained censorship in MM (2026-06) (Myanmar) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity censorship detected in Myanmar. Data sourced from OONI, CensoredPlanet.
Censorship Incident ID: MM-2026-0212. Severity: critical. Confidence: 77%